Students’ Attitude towards Biology in Secondary Schools in Islamabad, Pakistan - Ahmad, Shahzad; Sultana, Naveed; Jamil, Sadia (IJERI: International Journal of Educational Research and Innovation, 2022)
In this age of science and technology, the world is facing geographical challenges, whereas the future nation builders are losing their interest even in science subjects, especially, in biology. There are numerous factors that contributed towards students’ success in a particular subject but the most important one is their attitude towards that subject. The focus of the present study was to investigate the attitude of students towards Biology in Secondary Schools in Islamabad. The population of this study comprised all 10th grade Biology students in different institutions in Islamabad. Owing to the shortage of time, the researcher selected 506 students (from six public and four private schools) as a convenience sample for this study. These students were administered through a valid and reliable instrument known as “Biology Attitude Scale” (BAS) developed by the researcher. The study used a 5-point Likert type scale to measure students’ attitude towards Biology on seven dimensions: “Interest in Biology”, “Career in Biology”, “Importance of Biology”, “Biology Teacher”, “Difficulty in Biology”, “Equipment use in Biology” and “Methodology of Biology”. Students’ attitude toward Biology was analyzed by using the mean score of an individual statement. The findings of the study revealed that overall students showed a positive attitude towards Biology. Female students exhibited a positive attitude as compared to male students. Similarly, students in public schools showed a positive attitude toward students of private schools.